Oxidation of Methyl Orange Solution with Potassium Peroxydisulfate - Jun bo Zhong; Jian zhang Li; Yan Lu; Sheng tian Huang; Wei Hu (Iranian Journal of Chemistry & Chemical Engineering, 2012)
Oxidation of Methyl Orange (MO) solution in potassium peroxydisulfate (KPS) homogeneous reaction system without UV irradiation was investigated. The result shows that decolorization of MO increases as the dosage of K2S2O8 increases. The kinetic results demonstrate that the decolorization reaction is a pseudo first-order reaction when the concentration of MO is below 10 mg/L and Langmuir–Hinshewood kinetic model (L-H) can well described it, the value of Ea is 19.5 kJ/mol. The decolorization efficiency is low when the pH value is low (≤2). Result of CODCr shows MO can be effectively mineralized with KPS direct oxidation. The knowledge on the kinetics of the system and influence of some parameters on the system possesses both practical and theoretical values.